Dynamical response of the non-linear vibration of single-walled carbon nanotubes. (1st October 2009) - Khan, Ayub; Goel, Niti; Khan, Samina; Husain, M.
Dynamical response in single-walled carbon nanotubes (SWNTs) has been investigated through analytical and computational techniques. Analytically, an explicit expression for a formal control term has been estimated by using the Lie transforms. Computational studies reveal the suppression of chaos, which is in good agreement with the analytical investigations. And, our system follows regular patterns after the inclusion of control term.